Worlding America : a transnational anthology of short narratives before 1800 - Scheiding, Oliver; Seidl, Martin (Martin Johannes) (Stanford University Press, 2014)
Worlding America explores the circulation of short narratives in the early Americas through a combination of neglected primary materials and scholarly commentary. Building on recent reconsiderations of American literature in light of transnational and hemispheric approaches, it follows the migration of stories from various backgrounds and demonstrates how forms and themes developed in a new literary market that spanned the Atlantic world. While short narratives prior to 1800 have been largely excluded from critical discussions as well as anthologies, they give insight into the conditions of pub.